SERUM LEAD LEVELS IN FEMALE AGRICULTURAL FARM-WORKERS FROM BAHAWALPUR, PAKISTAN - Raziq, Muhammad Abdul; Khan, Muhammad Imran; Sipra, Muhammad Wajid Khurshid; Iqbal, Tehseen; Tariq, Sundus; Aslam, Maria (Pakistan Journal of Physiology, 2022)
Background: Lead (Pb) is a heavy metal present in our environment in soil, drinking water, air, petroleum products, insecticides and pesticides, and is excreted in body secretions like breast milk, saliva, semen, and sweat. We studied serum lead levels in lactating female farm workers of Bahawalpur who are exposed to various chemicals that contain lead arsenate. Methods: This study was conducted in the Department of Physiology, University of Health Sciences, Lahore after approval from the Ethical Review Committee. After informed consent, blood samples of 2.5 ml each from a total of 91 lactating mothers were collected. Serum lead levels were determined by Inductively Coupled Plasma Spectrophotometry (ICP). Results: High lead levels were detected in 90 out of 91 (98.90%) women. Mean serum lead levels were 61.05±29.59 µg/L. Conclusion: The serum lead level was considerably higher than the WHO allowable level in our study population. Pak J Physiol 2022;18(1):36?8